Characterization by MALDI Mass Spectrometry of Cucurbit[n]uril (n = 6,7,8) - María Emilia Dueñas (ACI Avances en Ciencias e Ingenierías, 2011)
The characterization of a mixture of cucurbit[n]uril (n = 6,7,8) was carried out by MALDI MS (Matrix-assisted Laser Desorption/Ionization Mass Spectrometry Mass Spectrometry). The solid mixture of the titled compounds was synthesized as part of a research study involving supramolecular chemistry at the Departamento de Química e Ingeniería Química at USFQ. For the MALDI analysis, an appropriate procedure was implemented for sample preparation, which includes the effective dissolution of the solid mixture of cucurbit[n]uril in a solution of water and formic acid, and the addition of alpha-cyano-4-hydroxy cinamic acid as MALDI matrix (10g/l in 70:30 (v:v) of methanol: acetonitrile). In the sample preparation process for MALDI, other solvents were employed to try dissolving the cucurbit[n]uril mixture with poor results. The addition of formic acid to deionized water was important to achieve satisfactory dissolution of the cucurbit[n]uril compounds and to assure its compatibility with the matrix. To acquire the corresponding mass spectra, a MALDI-Time-of-Flight Mass Spectrometer (MALDI-TOF MS) was used, which was built in the Departamento de Física at EPN. The mass spectra of the detected cucurbit[n]uril ions were characterized by the presence of the single protonated peaks of three molecular species corresponding to n = 6,7,8 as inferred from their m/z values. Additionally, the mass spectra contained abundant peaks of the MALDI matrix in the mass region up to 500 Da. The mass spectra were satisfactorily internally calibrated with the help of multiple peaks of a PEG600 polymer that was introduced as an internal standard in the sample. The instrumental molecular mass resolution allowed for isotopical resolution over the whole mass range and the overall mass accuracy was about 0.1 %. The most intense signal among the cucurbit[n]uril peaks was assigned to the cucurbit[7]uril compound. A discussion is advanced to rationalize the observed molecular cucurbit[n]uril species under the used methodology.